Publication trends and levels of evidence in obstructive sleep apnea literature. (4th January 2018) - Gouveia, Christopher J.; Zaghi, Soroush; Awad, Michael; Camacho, Macario; Liu, Stanley Y. C.; Capasso, Robson; Kern, Robert C.
Abstract : Objectives/Hypothesis: Examine trends in clinical research and levels of evidence related to obstructive sleep apnea (OSA) in the medical literature. Describe the features and trends of OSA research within otolaryngology journals. Study Design: Retrospective analysis. Methods: Review of OSA research articles from 2006, 2011, and 2016 in four leading medical sleep and otolaryngology journals. Level of evidence was graded, and study characteristics were measured. Results: Seven hundred eight total articles were reviewed. OSA articles significantly increased in both number and proportion of total articles in the medical sleep ( P < .001) and otolaryngology ( P = .004) journals. Surgically focused articles did not significantly increase in either literature. There was no significant difference between medical sleep and otolaryngology literature levels of evidence regarding OSA, and no trend toward higher levels of evidence over time. Medical sleep publications had significantly higher proportions of grant‐funded ( P < .001) and National Institutes of Health (NIH)–funded ( P < .001) publications versus otolaryngology journals. Over time, otolaryngology journals had decreasing numbers of grant‐funded and NIH‐funded projects. Conclusions: OSA research is increasingly present in medical sleep and otolaryngology literature. Levels of evidence are modest for the two specialties, and have shown no trend toward increasing over time. Concurrently, otolaryngologists are less likely to be grant funded than their medical colleagues, and sleep surgery has stagnated in the studied journals. This study encourages continued efforts to publish high‐quality research on OSA. It may also help guide our specialty when setting priorities regarding research funding and support for sleep surgeons. Level of Evidence: NA Laryngoscope, 128:2193–2199, 2018